Chronic Disease Surveillance in Alberta’s Tomorrow Project using Administrative Health Data - Ming Ye (Swansea University, 2021)
Introduction Alberta's Tomorrow Project (ATP) is the largest population-based prospective cohort study of cancer and chronic diseases in Alberta, Canada. The ATP cohort data were primarily self-reported by participants on lifestyle behaviors and disease risk factors at the enrollment, which lacks sufficient and accurate data on chronic disease diagnosis for longer-term follow-up.